Pengaruh pemberian nano daun kelor (moringa oleifera) terhadap kadar mineral serum dan tulang pada tikus sprague dawley jantan tumbuh - Syahrial, Syahrial; Rimbawan, Rimbawan; Damayanthi, Evy; Astuti, Dewi Apri; Suptijah, Pipih (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2019)
Background: One of the important minerals for growth is calcium to build new bone. Moringa oleifera has been known as high nutritional content and bioactive compound tree that could act as antioxidant and improved several diseases like diabetes, arthritis, cardiovascular. Phytochemical analyses have shown that Moringa oleifera contain of high macro minerals like calcium, potasium, magnesium, and phosphor. Several previous studies have shown that mineral nanoparticle have higher bioavailability than natural compounds.. Objectives: The purpose of this study was to analyze the effect of moringa oleifera nanoparticle leaf on mineral serum and bone at growth stage of Sprague Dawley male rats. Methods: In this study, the pre and post controlled group design and complete random design was used. The subjects were 27 growing male Sprague dawley rats aged 2 month were devided into three group which received standard feed contain CaCO3 (control group), intervention feed contained 450nm and 750nm nano Moringa oleifera for 60 days. The data of the experiment was analyzed by paired T-test and Duncan test at 95% confidence level.Results: The result showed that there was no significance different for both of intervention group for mineral serum and fermur bone. While for the tibia bone, the result showed that the calcium, phosphor and magnesium were significantly increase (p<0.05). The intervention group received 450nm showed more effective improvement of magnesium level (p<0.05) than intervention group received 750nm.Conclusion: The intervention of moringa oleifera nanoparticle leaf had a positive effect in decreasing serum and bone mineral levels in male rats. There were significant increased at magnesium level measured in tibia bones after intervention, with higher increasing at group received 450nm nanoparticle.